A comparative analysis of abandoned street children and formerly abandoned street children in La Paz, Bolivia. Issue 9 (20th August 2004) - Huang, C-C; Barreda, P; Mendoza, V; Guzman, L; Gilbert, P
Abstract : Aims and Methods: A comparative study of abandoned street children and formerly abandoned street children was conducted in La Paz, Bolivia, representing the first such comparative assessment. Between August and December 1997, all abandoned street children in La Paz, Bolivia, who were willing to participate (n = 124) were interviewed repeatedly at night using standardised questionnaires to collect information on family history, demographics, socioeconomics, drug use, and physical/sexual abuse. The same questionnaires were administered to all former abandoned street children who chose to enter a local orphanage (n = 35). Results: The persistent street children differed greatly from those who entered the orphanage, most markedly in their higher risk of police abuse (95% versus 38%), absence from school (84% versus 19%), engagement in robbery (26% versus 4%), paint thinner use (88% versus 41%), alcohol use (58% versus 12%), and a serious medical problem (53% versus 20%). The risks for street children increased rapidly with age. Conclusions: A cascade of adverse outcomes afflicts the vast majority of abandoned street children in La Paz, which cumulate with age and diminish the likelihood of successful rehabilitation through lasting placement in an orphanage or residential home. Informed by these findings, the investigators operate a home for abandoned street children in La Paz.